Negative regulators of TGF-β1 signaling in renal fibrosis; pathological mechanisms and novel therapeutic opportunities. Issue 2 (29th January 2021) - Gifford, Cody C.; Tang, Jiaqi; Costello, Angelica; Khakoo, Nidah S.; Nguyen, Tri Q.; Goldschmeding, Roel; Higgins, Paul J.; Samarakoon, Rohan
Abstract: Elevated expression of the multifunctional cytokine transforming growth factor β1 (TGF-β1) is causatively linked to kidney fibrosis progression initiated by diabetic, hypertensive, obstructive, ischemic and toxin-induced injury. Therapeutically relevant approaches to directly target the TGF-β1 pathway (e.g., neutralizing antibodies against TGF-β1), however, remain elusive in humans. TGF-β1 signaling is subjected to extensive negative control at the level of TGF-β1 receptor, SMAD2/3 activation, complex assembly and promoter engagement due to its critical role in tissue homeostasis and numerous pathologies. Progressive kidney injury is accompanied by the deregulation (loss or gain of expression) of several negative regulators of the TGF-β1 signaling cascade by mechanisms involving protein and mRNA stability or epigenetic silencing, further amplifying TGF-β1/SMAD3 signaling and fibrosis. Expression of bone morphogenetic proteins 6 and 7 (BMP6/7), SMAD7, Sloan–Kettering Institute proto-oncogene (Ski) and Ski-related novel gene (SnoN), phosphate tensin homolog on chromosome 10 (PTEN), protein phosphatase magnesium/manganese dependent 1A (PPM1A) and Klotho are dramatically decreased in various nephropathies in animals and humans albeit with different kinetics while the expression of Smurf1/2 E3 ligases are increased. Such deregulations frequently initiate maladaptive renal repair including renal epithelial cell dedifferentiation and growth arrest, fibrotic factor (connective tissue growth factor (CTGF/CCN2), plasminogen activator inhibitor type-1 (PAI-1), TGF-β1) synthesis/secretion, fibroproliferative responses and inflammation. This review addresses how loss of these negative regulators of TGF-β1 pathway exacerbates renal lesion formation and discusses the therapeutic value in restoring the expression of these molecules in ameliorating fibrosis, thus, presenting novel approaches to suppress TGF-β1 hyperactivation during chronic kidney disease (CKD) progression.